Asymmetrical grounded CPW‐fed antenna for WLAN applications. Issue 11 (26th August 2013) - Dinesh, R.; Vinod, V. K. T.; Sarin, V. P.; Shameena, V.A.; Mohanan, P.
ABSTRACT A novel compact asymmetrical grounded coplanar waveguide‐fed antenna for dual‐band operation is presented. The modified asymmetric ground and slit on the radiating element provides dual band covering 2.4 and 5.2 GHz WLAN operation. A prototype of proposed antenna has been fabricated and tested. The antenna offers omnidirectional radiation pattern at 2.4 GHz and directional radiation pattern at 5.2 GHz. The peculiarity of the design is that each band can be independently tuned by varying the current paths. The antenna has an overall dimension of 26.5 × 5.7 × 1.6 mm3 when printed on a substrate of relative permittivity 4.4. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2739–2741, 2013